The moral and political worlds of Macbeth - Kabal, Lamia. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
Unlike Shakespeare’s greatest villains such as Richard III and Iago, Macbeth is not really comfortable in his role as murderer and usurper thanks to his acute awareness that he is acting against the moral and political values which underpin the social fabric. The aim of this thesis is to explore the ways in which Macbeth falls afoul of the commonly accepted ethical and political norms in the discourse of the Renaissance era and finds himself in the role of a would-be "Machiavel". He puts ‘words’ and his imagination into use to seize power and later to maintain his status as king of Scotland. Macbeth emerges as a great exemplar of how desire for political power silences the claims of conscience.